The novel of (Blogs of the conscience -I am) by Sadoon Muhsin Dhamad. A critical approach in text and footnotes. - م. د علي حسن هذيلي (Thi Qar Arts Journal, 2021)
We mean about the footnotes the thresholds that preceded or appended the seven blogs (chapters), which formed the text of ((addamad)) novel, which means what was written on the first and last covers, and what was illustrated in these memories about the stages that the hero passed through, in spite of that they were more or less mental stages nearer to the edge of hallucination than to the reality or fantasy. This was confirmed by dhamad himself when he said that his novel neither a fantasy nor a reality. We introduce this to can read the text by footnotes or the contrast, starting from the strong relation between them. So, the article consisted of introduction and to researches, we talked in the introduction about the relation of the title with the entitled. For the blogs of conscience -I am- mean that the novel would be like Biography that the writer talks of himself in it. In the first research we use one of this blogs to prove that it was truly like hallucination and never approach the narration at all. In the second research we imagined a dialogue between the great novelists and critics about dhamad novel and his announcements which dissented the normality like his saying that his novel is neither a reality nor a fantasy. The conclusion was including the most important result that the non-novelists became novelists may be because of democracy which opened the door to the all